From the Outside In : Suburban Elites, Third-Sector Organizations, and the Reshaping of Philadelphia - Adams, Carolyn Teich (Cornell University Press, 2014)
In From the Outside In, Carolyn T. Adams addresses the role of suburban elites in setting development agendas for urban municipalities and their larger metropolitan regions. She shows how major nongovernmental, nonmarket institutions are taking responsibility for reshaping Philadelphia, led by suburban and state elites who sit on boards and recruit like-minded suburban colleagues to join them. In Philadelphia and other American cities, Third Sector organizations have built and expanded hospitals, universities, research centers, performing arts venues, museums, parks, and waterfronts, creating whole new districts that are expanding outward from the city's historic downtown. The author draws on three decades of scholarship on Philadelphia and her personal experience in the city's nonprofit world to argue that suburban elites have recognized the importance of the central city to their own future and have intervened to redevelop central city land and institutions. Suburban interests and state allies have channeled critical investments in downtown development and K-12 education. Adams contrasts those suburban priorities with transportation infrastructure and neighborhood redevelopment, two policy domains in which suburban elites display less strategic engagement. From the Outside In is a rich examination of the promise and difficulty of governance that is increasingly distinct from elected government and thus divorced from the usual means of democratic control within an urban municipality.